A novel hydrazide Schiff base self-assembled nanoprobe for selective detection of human serum albumin and its applications in renal disease surveillance. Issue 36 (14th August 2020) - Wang, Zhi-Gang; Yan, Xiao-Jing; Liu, Hai-Bo; Zhang, De-Long; Liu, Wei; Xie, Cheng-Zhi; Li, Qing-Zhong; Xu, Jing-Yuan
Abstract : A novel fluorescent probe based on disassembly-induced emission and the site-binding mechanism for HSA detection and applications in renal disease surveillance. Abstract : Human serum albumin (HSA) is considered as a biomarker for the early diagnosis of renal disease, therefore identifying and detecting HSA in biological fluids (especially urine) with an easy method is of great importance. Herein, we report a novel hydrazide Schiff base fluorescent probe N ′-((7-(diethylamino)-2-oxo-2 H -chromen-3-yl)methylene)pyrazine-2-carbohydrazide (NPC ), which self-assembled into nanoparticles in aqueous solution. Based on disassembly-induced emission and the site-specific recognition mechanism, the binding of NPC with HSA resulted in a fluorescence "turn-on" response. Probe NPC exhibited superior selectivity and sensitivity toward HSA with a detection limit of 0.59 mg L −1 in PBS and 0.56 mg L −1 in the urine sample. The site-binding mechanism of NPC with HSA was explored by fluorescence quenching study, Job's plot analysis, HSA destruction, site marker displacement and molecular docking. Fluorescence imaging of HSA in MCF-7 cells was achieved by using a non-toxic NPC probe, suggesting that NPC could be applied to visualize the level of HSA in vivo . More importantly, further practical applications of probe NPC in human urine samples were achieved with satisfactory results by using a fluorometer or test paper, which could provide extensive application in clinical diagnosis.